GENDER DIVERSITY, BOARD SIZE, AND FIRM AGE ON FORWARD-LOOKING INFORMATION DISCLOSURE AND ITS IMPACT ON FUTURE PROFITABILTY - Hanifah Nur Hidayati; Dewita Puspawati (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective –  This study aims to determine the effect of gender diversity on board, board size, and firm age on forward-looking information disclosure in the company's financial statements. In addition, it is also to determine the impact of forward-looking information disclosure on future profitability. Design/Methodology/Approach – The method used in this research is a quantitative approach. Using purposive sampling technique, the final sample is 122 samples of manufacturing companies listed on the IDX during the 2020-2022 period. The data was processed using multiple regression analysis using by SPSS 25 software. Findings – This study found that gender diversity and board size variables have no effect on forward-looking information disclosure. Meanwhile, firm age has a significant negative effect on forward-looking disclosure. This study also found that forward-looking disclosure has a positive effect on future profitability. Conclusion and Implications – This study shows that among gender diversity, board size and firm age, only firm age has an effect on forward-looking information disclosure. In addition, this study shows that forward looking disclosure also plays an important role in improving financial performance and market reputation.